Responding to service failures with prevention framed donations. Issue 5 (28th August 2019) - Alhouti, Sarah; Wright, Scott A.; Baker, Thomas L.
Abstract : Purpose: Service failures are common and companies must decide how best to respond to these incidents. The purpose of this study is to examine service recovery efforts that incorporate a donation component, in addition to financial compensation. More specifically, the relative effectiveness of these recovery efforts was explored according to the regulatory focus framing (i.e. prevention- or promotion-focused) of the donation message. Design/methodology/approach: Three experiments are conducted to test the hypotheses. Findings: Drawing from regulatory focus theory (Higgins, 1997), the authors determined that prevention framing (e.g. highlighting the negative outcomes avoided by a donation) leads to better service recovery outcomes compared to promotion framing (e.g. highlighting the positive outcomes of a donation) the donation message. Furthermore, warmth (e.g. perceptions of caring and helpfulness) and competence (e.g. perceptions of capability and usefulness) underlie this effect and message trust moderates the effect of regulatory framing on warmth. Research limitations/implications: This study offers several theoretical and managerial implications. First, a novel recovery approach that benefits multiple stakeholders was illustrated, particularly when the donation message is prevention (vs promotion) framed. The authors focused on donations in particular, but future researchers should explore other corporate social responsibility activities such as those pertaining to sustainability, ethical labor practices or educational training. Practical implications: Companies should consider incorporating donations into service recovery efforts. Moreover, companies should use prevention as opposed to promotion frames in their donation messages. Using a prevention frame enhances perceptions of company warmth and competence. Originality/value: Very little research has explored the effectiveness of donations following service failures despite evidence that companies use donations in this context. This research highlights the importance of regulatory focus framing and demonstrates how a donation, paired with financial compensation, is more/less effective according to the framing of the communication. Thus, this research demonstrates a novel effect, identifies its underlying mechanism through warmth and competence and establishes an important boundary condition according to message trust.